EP874 Serologic markers of Chlamydia trachomatis and other sexually transmitted infections and subsequent ovarian cancer risk: results from the EPIC cohort. (1st November 2019) - Idahl, A; Le Cornet, C; González Maldonado, S; Waterboer, T; Bender, N; Tjønneland, A; Hansen, L; Boutron-Ruault, M-C; Fournier, A; Kvaskoff, M; Boeing, H; Trichopoulou, A; et al.
Abstract : Introduction/Background: Sexually transmitted infections (STI) and pelvic inflammatory disease may cause damage to the fallopian tube where a substantial proportion of epithelial ovarian cancer (EOC) likely arises. The aim of this study was to determine whether Chlamydia trachomatis antibodies are associated with higher EOC risk. As secondary objectives, we investigated Mycoplasma genitalium, herpes simplex virus type 2 (HSV-2) and human papillomavirus (HPV) 16, 18 and 45 and EOC risk. Methodology: In a nested case-control study within the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort, 791 cases and 1, 669 matched controls with pre-diagnosis blood samples were analyzed. Cases and controls were matched on study center, and at blood collection age, time of day, fasting status, exogenous hormone use, menopausal status, and menstrual cycle phase. Antibodies against C. trachomatis, M. genitalium, HSV-2, and HPV 16, 18 and 45 (E6, E7, L1) were assessed using multiplex fluorescent bead-based serology. Conditional logistic regression was used to estimate relative risks (RR) and 95% confidence intervals [CI] comparing women with positive vs. negative serology. Results: A total of 40% of the study population was seropositive to at least one STI. Positive serology to C. trachomatis Pgp3 antibodies was not associated with EOC risk overall, but was associated with higher risk of the mucinous histotype (RR=2.56 [95% CI=1.3–5.05]). Positive serology for chlamydia heat shock protein 60 (cHSP60-1), produced during persistent infection, was associated with higher risk of EOC overall (1.33 [1.09–1.62]) and of the serous subtype (1.42 [1.09–1.84]). None of the other evaluated STIs were associated with EOC risk overall; in analyses by histotype, HSV-2 was associated with higher risk of endometrioid EOC (2.93 [1.50–5.74]). Conclusion: C. trachomatis infection may influence carcinogenesis of serous and mucinous EOC, while HSV-2 might promote endometrioid disease. Mechanisms linking STIs to EOC need to be further elucidated. Disclosure: Financial support: This work was supported by grants from The Cancer Research Foundation in Northern Sweden and The County Council of Västerbotten, Sweden, and the German Cancer Research Center. The coordination of EPIC is financially supported by the European Commission (DG-SANCO) and the International Agency for Research on Cancer. The national cohorts are supported by grant givers in the separate countries. Detailed information on demand.